Health and its Social Determinants: A Study on Health Inequalities among Tabriz Citizens - Hossein Benifatemeh; Mohammed Bagher Alizade Aghdam; Jafar Shahamfar; Bahman Abdi (جامعه شناسی کاربردی, 2014)
Introduction Health is one of the most important needs of humans. Healthy people can perform social roles completely and in competition with others can obtain good positions. For this reason, attention to health and its distribution is one of the most interesting fields of investigation in sociology, because it is related to social justice and good governance in all societies. On the other hand, health inequalities exist in all societies and countries. New studies show that inequalities in health distribution are deepened in recent years among different groups of people inside countries, among poor and reach countries alike. These observations and scientific facts confronts sociologists with very important and basic question. What are the reasons of these health inequalities? After World War II, sociologists entered to medical institutions and universities and studied health problems in order to answer this important question. They stated that if health, illness and disease were entirely biological in origin then we would expect the incidence to be similar across geographical locations and social groupings. However this is not the case and the social patterns of health provides evidence that disease and illness do not affect all sectors of society equally.